Seroprevalence of SARS-CoV-2 virus infection in employees in the health insurance sector - Dragan Spaić; Anđela Mandić; Biljana Mijović; Srdjan Mašić; Dejan Bokonjić; Dragana Puhalo Sladoje (Биомедицинска истраживања, 2021)
Introduction: Serological testing for SARS-CoV-2 virus infection is a valuable method of estimating the extent of COVID-19 disease prevalence. The study aims to assess the seroprevalence of SARS-CoV-2 virus infection in a specific group of respondents employed in the health insurance sector, to determine the ratio of symptomatic and asymptomatic cases, as well as to examine susceptibility to COVID-19 in relation to the ABO blood group system. Methods: This research was conducted among 150 randomly selected employees from the health insurance sector of the Republic of Srpska. All respondents completed the survey, voluntary consent to participate, and had a blood sample taken. Serum samples were tested for the presence of SARS-CoV-2 specific IgG antibodies. Results: The seroprevalence of SARS-CoV-2 virus infection was 70.7%. Out of the 100 seropositive respondents, 48% had the presence of a symptom of COVID-19, while 52% had no symptoms of the disease in the period from 1 March 1 2020 until the day of testing. Examining the association between ABO blood group system and seropositivity in our study, we found that the highest seroprevalence of SARS-CoV-2 IgG antibodies among respondents was in blood group B (83.3%), followed by blood group AB (80.0%) and blood group A (75.0%), while the lowest seroprevalence was among respondents with blood group O (54.1%). Conclusion: Among employees in the health insurance sector, SARSCoV-2 seroprevalence of 70.7% was registered. Among respondents with a positive serological result on IgG, 52% were asymptomatic. The seroprevalence of SARS-CoV-2 virus infection is the lowest among subjects with blood group O.
Keywords: COVID-19; seroprevalence; healthcare professionals; blood types